Barometer logging reveals new dimensions of individual songbird migration. (17th September 2018) - Sjöberg, Sissel; Pedersen, Lykke; Malmiga, Gintaras; Alerstam, Thomas; Hansson, Bengt; Hasselquist, Dennis; Thorup, Kasper; Tøttrup, Anders P.; Andersson, Arne; Bäckman, Johan
Abstract : Recent advances in tracking technology are based on the use of miniature sensors for recording new aspects of individual migratory behaviour. In this study, we have used activity data loggers with barometric and temperature sensors to record the flight altitudes as well as ground elevations during stationary periods of migratory songbirds. We tracked one individual of red‐backed shrike and one great reed warbler along their autumn migration from Europe to Africa. Both individuals performed their migration stepwise in travel segments and climbed most metres during the passage across the Mediterranean Sea and the Sahara Desert and least metres during the first flight segment in Europe. The great reed warbler reached its highest flight altitude of 3950 m a.s.l. during the travel segment from Europe to west Africa, while the red‐backed shrike reached 3650 m a.s.l as maximum flight altitude during its travel segment from Sahel to southern Africa. Both individuals used both lowlands and highlands for resting periods along their migrations. Furthermore, temperature decreased with increasing altitude during migratory flights for both individuals, highlighting the potential to determine flight duration from temperature measurements. Finally, we discuss how barometric data could be used to investigate birds' responses to changes in air pressure as a cue for departures on migratory flights. This new technique, i.e. using a miniature data logger with barometric pressure sensor to estimate flight altitudes and ground elevations, will open up new avenues for research and importantly advance our understanding on how small birds behave during migratory flights.